Attrition in IT-BPO : A Critical Appraisal in Indian Context: The Alarming Cost and Less Competitive Advantage - Nigam, Ashutosh (Journal of Commerce and Trade, 2007)
Attrition in IT-BPO not only pushes up costs incurred on the training of employees but also affects productivity that too with the ideal level of ‘Knowledge maturity’ of the organization and the employees. The organizations having capacity to withstand its long lasting relationship with employees would survive in the marked place and others would fade away in the long run. The final solutions of IT-BPO lies in the stabilization of business operation and availability of trained and matured manpower in abundance and which may bring sustainable solution for the high attrition in the sector. The commitment of employees at all levels will help the industry to stabilize, grow and add value to the economic growth.